Multistage carcinogenesis in the urinary bladder. - Cohen, S M (1983)
The induction of cancer of the urinary bladder is a multi-stage process involving multiple exogenous and endogenous factors. Based on the classical initiation-promotion model, we have used N-[4-(5-nitro-2-furyl)-2-thiazolyl]formamide (FANFT) as initiator and sodium saccharin (SAC) or tryptophan as promoters. These latter chemicals have the properties expected of promoters: induction of hyperplasia, reversibility and nonmutagenicity. Also, tumors were induced whether the promoter was administered immediately after FANFT or beginning 6 weeks after FANFT was discontinued, but no tumors resulted if either promoter was given without initiation with FANFT. Factor(s) present in normal urine also are involved in the promotion process, in addition to the role of urine as a carrier of carcinogens. However, administration of SAC to animals with a rapidly proliferating bladder mucosa, induced by ulceration, pellet insertion, or in utero, resulted in bladder tumor induction, even without prior initiation with FANFT. To better understand the complex interaction of the multiple variables in bladder carcinogenesis, a stochastic computer model has been formulated based on long-term carcinogenicity and tissue kinetic studies in vivo. This model indicates the importance of cell proliferation and the development of hyperplasia in carcinogenesis.